PROFITABILITY, LEVERAGE RATIO, AND LIQUIDITY TO COMPANY VALUE WITH GENDER DIVERSITY AS MODERATION VARIABLES - Dwi Aprillia Rahmawati; Nurasik; Sarwenda Biduri (International Journal of Business, Law and Political Science, 2025)
Objective: The purpose of writing this study is to find out whether the Gender Diversity variable can moderate the variables of profitability, leverage ratio, and liquidity to the value of the company. Method: The population in this study is manufacturing companies in the goods and consumption industry sector for the period 2017-2023. The sample was selected using the purposive sampling method and obtained 180 companies. The data analysis technique used is the outer model to test the validity and reliability of the data and the inner model to test the hypothesis using the SmartPLS analysis tool version 3.0. Results: The results of this analysis show that profitability and leverage ratio affect the company's value. Meanwhile, the liquidity variable has no effect on the company's value. The gender diversity variable is able to moderate profitability to company value. Meanwhile, the gender diversity moderation variable is not able to moderate the influence of leverage ratio and liquidity on the company's value. Novelty: The study investigates the moderating role of gender diversity in the relationship between profitability, leverage ratio, liquidity, and company value, offering new insights into the impact of gender diversity on corporate performance.